Origen micótico de asma bronquial en pacientes de 2 a 12 años. Centro de Asma-Alergias Muñoz, 2017-2019 - Diana Mireya, Oña Muso (2019)
Objective: To define the fungal etiology of bronchial asthma by means of the Prick test method, as well as to determine the prevalence of the allergens Hormodendro, Alternaria, Aspergillus, Mucor and Penicillium in children from 2 to 12 years old who came for treatment with immunotherapy at Muñoz Center of Asthma and Allergies in the period 2017-2019. Material and Methods: The study was carried out based on the research methodology with a descriptive study, in a universe of 322 patients, obtaining data from the review of medicales records, patient records and laboratory results record of the Prick method -test at Muñoz Center of Asthma and Allergies Results: Of the 322 patients under study with a diagnosis of bronchial asthma, the main etiologic agents are fungal allergens with 197 cases, equivalent to 61.18%, this group is divided into patients who have an allergic reaction specifically to pure fungal allergens with 64 cases, equivalent to 32.49% and patients with allergic reaction to combined fungal allergens (pollens, grasses, weeds, dust, epithelium, wool and tobacco, with 133 cases equivalent to 67.51%. Conclusion: The main fungal agents detected by the Prick-test method that develop bronchial asthma in children from 2 to 12 years old who visited Muñoz Center of Asthma and Allergies, are the Hormodendron, Aspergillus and Alternaria.